Genome Wide Identification of Terpenoid Metabolism Pathway Genes in Chili and Screening of Key Regulatory Genes for Fruit Terpenoid Aroma Components - Mengxian Yang; Kun Wu; Genying Fu; Shuang Yu; Renquan Huang; Zhiwei Wang; Xu Lu; Huizhen Fu; Qin Deng; Shanhan Cheng (Horticulturae, 2025)
Aroma is an important processing and consumption quality trait of fruits and vegetables, and terpenes produced from the terpenoid metabolic pathway are a critical component of chili fruit flavor. This pathway involves the participation of at least eighteen enzymes, such as AACT, HMGS, HMGR, MVK, PMK, MVD, FPPS, GGPPS, DXS, DXR, MCT, CMK, MECPS, HDS, HDR, GPPS, IDI, and TPS. In this study, the genome wide information, expression characteristics, and relationship with terpenoids of terpenoid pathway genes are analyzed in C. annuum. The results showed that C. annuum has sixty-seven genes related to terpene metabolic pathways. Non-targeted metabolomics studies found that the content of aromatic terpenoids α-calacorene, α-cubene, and cis-β-farnesene increased with fruit development in HDL fruits, while linalool and nerolidol were much higher in GLD608. Correlation analyses between qRT-PCR and metabolome data showed that the expression levels of CaHMGS-3, CaMVD-1, CaCMK-1, and CaGGPPS-2 were positively correlated with the content of linalool, a flavor monoterpene alcohol. CaMECPS-1 was positively correlated with cis-β-farnesene, and there was also a significant positive regulatory relationship between CaTPS-5 and nerolidol relationship. In conclusion, the present study provides genetic resources for further studies on the gene regulatory mechanisms of flavor synthesis and terpenoid metabolic pathways in chili.